2009
DOI: 10.1007/s00586-009-0925-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging anatomy and variation of vertebral artery and bone structure at craniocervical junction

Abstract: The objective of this article is to display the vertebral artery and bone structure at the craniocervical junction (CJVA and C(0-1-2)) with three-dimensional CT angiography (3DCTA) and identify their anatomic features and variations. Eighty-eight subjects without pathology of vertebral artery (VA) and C(0-1-2) were selected from head-neck CTA examination. 3D images were formed with volume rendering (VR) and multiplanar reconstruction (MPR). On the 3D images, CJVA and C(0-1-2) were measured, and their variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 22 publications
(27 reference statements)
1
18
0
1
Order By: Relevance
“…This dangerous condition may also emerge in extreme head postures. It should also be considered that the route of the vertebral artery at the craniovertebral junction is complex because the artery usually forms five curves with frequent variations (Duan et al 2009). Therefore, bone abnormalities as well as arterial abnormalities can, singly or in combination, cause a reduction in cerebral blood flow.…”
Section: Arcuate Foramenmentioning
confidence: 99%
“…This dangerous condition may also emerge in extreme head postures. It should also be considered that the route of the vertebral artery at the craniovertebral junction is complex because the artery usually forms five curves with frequent variations (Duan et al 2009). Therefore, bone abnormalities as well as arterial abnormalities can, singly or in combination, cause a reduction in cerebral blood flow.…”
Section: Arcuate Foramenmentioning
confidence: 99%
“…Vertebral arteries enter the TF at the C6 level (1). In previous studies, the size, number, and form variations of TFs were observed and morphometric measurements were done on dry cadaveric materials (2)(3)(4)(5)(6). In the previous studies, it was reported that multidetector computed tomography (MDCT) with 3-dimensional (3D) volume rendering (VR), multiplanar reconstruction (MPR), and maximum intensity projection (MIP) techniques has a very high sensitivity in evaluating anatomic (bony and vascular) variations and anatomic localization (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…9 , 12 , 19 Moreover, many anatomical and structural variations exist in the craniovertebral junction. 20 Lee et al 21 analyzed CT scans in terms of the entry point and trajectory of C0-C1 transarticular screw and concluded that C0-C1 transarticular screw fi xation was possible in up to 98% of 126 patients. The feasibility of occipital condyle screw placement under fl uoroscopic guidance 12 or prior 3-dimensional planning 5 has been recently studied in cadaver heads.…”
Section: Discussionmentioning
confidence: 99%